Attention-deficit hyperactivity disorder in spontaneously hypertensive rat strain SHR/NCrl is associated with specific expression of uncoupling proteins, glucose transporter 1 and BACE1 - Sato, Tsunehisa; Schreckenberg, Rolf; Schlüter, Klaus-Dieter (Frontiers in Cellular Neuroscience, 2025)
Attention-deficit hyperactivity disorder (ADHD) is the most prevalent neurodevelopmental disorder worldwide. To improve treatment strategies against ADHD a better understanding of underlying pathophysiology is required. Spontaneously hypertensive rats (SHR) from the strain SHR/NCrl are a suitable rodent model of ADHD. Here we compared the gene expression in the brains of SHR/NCrl strain to that of other genetically related hypertensive and normotensive rat strains that do not show an ADHD phenotype. In addition, the impact of physical activity on genes that display such differences was also addressed because high physical activity is one non-pharmacological option to cure ADHD symptoms. RNA was isolated from the medulla oblongata, the olfactory bulb, and the cortex. Gene expression was analyzed by qRT-PCR. The cortical expression of GLUT1 was also analyzed by Western Blot. Physical activity was improved by free access to running wheels for six months. Female rats were used in this study and sacrificed at the age of 7.5 months. The results show that gene expression in SHR/NCrl differs from other SHR strains in the olfactory bulb, medulla oblongata, and the cortex. Main differences were obtained for SLC25A14, coding for the protein UCP5, SLC2A1, coding for the protein glucose transporter (GLUT) 1 in the cortex and CCL2 and for BACE1 in the medulla oblongata. The expressions of SLC25A14 and BACE1 in the medulla oblongata were normalized in physical active rats. Our study further underlines the usefulness of the SHR/NCrl strain as an ADHD animal model when combined with proper controls. Furthermore, this study identifies genes that are specifically down-regulated in the medulla oblongata of SHR/NCrl and that are affected by activity status.